Značilnosti tal in rastja na ploskvah intenzivnega monitoringa gozdnih ekosistemov - Urbančič, Mihej (Gozdarski vestnik, 2016)
This article describes characteristics of forest soil and vegetation on twelve sites, intended for intensive monitoring (IM) of forest ecosystems in Slovenia. Research sites, sized one hectare and divided into subplots, are situated on selected locations all over Slovenia. Six IM sites were founded on limestones and dolomites, two on noncalcareous plutonic rock (on base-poor grandiorite), and four on parent materials from unconsolidated sedimentary rock. We made soil profiles in the soil, sampled them by probing, described their morphological characteristics and performed lab (chemical and physical) analyses of soil samples. We classified the studied soil according to the Slovenian and international classification WRB (2006). The following soil types developed on the mainly carbonate moraines: rendzinas, eutric brown and leached soils (or WRB units: leptosol, (eutric) cambisol, luvisol). On the IM site, situated on predominantly non-carbonate alluvial and glacial gravels, the predominant soil type is dystric brown soil (dystric) cambisol). On the IM site, where the parental material is composed of pleistocene sediments and the soil is strongly affected by groundwater, we found hypogley and amphigley soils (gleysols), and alluvial soils (fluvisols) on alluvial sediments. Studies of vegetation comprised phytocoenological classification of vegetation and determination of plant species diversity on twelve IM sites. Phytocoenological classification of forest stands was performed on the basis of vegetation surveys, inspection of the wider area, and study of phytocoenological literature. Beech is the prevailing tree species on the half of study sites. Forests of Lamio orvalae-Fagetum association grow on three sites, and forests of Omphalodo-Fagetum, Seslerio autumnalis-Fagetum and Cardamini savensi-Fagetum associations cover one site each. Stands of lowland forest of pedunculate oak and common hornbeam (Querco roboris-Carpinetum s. lat. and Pseudostellario europaea-Quercetum roboris) grow on two IM sites. Four IM sites are covered with secondary forest of conifers (Aposerido-Piceetum, Avenello flexuosae-Piceetum, Seslerio autumnalis-Pinetum nigrae, Vaccinio myrtilli-Pinetum sylvestris). Plant species composition on permanent plots shows a relatively high degree of plant diversity, for 295 diverse species of pteridophytes and spermatophytes and 109 moss species were recorded on all 64 larger vegetation sub-plots in 2004.
Keywords: monitoring gozdov; gozdna tla; gozdna rastišča; gozdne združbe; Slovenia; Slovenija